ANALISIS PENGARUH PROFITABILITAS PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN PADA HUTANG JANGKA PENDEK, HUTANG JANGKA PANJANG, UMUR PERUSAHAAN DAN UKURAN PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2019 – 2021 - Fitrianti, Heffy Auliya (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Today the food and beverage industry sector companies are growing. The development of the company is correlated with profitability, considering that profitability is an important factor for the sustainability of the company. The purpose of this study was to analyze the effect of short-term debt, long-term debt, company age, and company size on company profitability. This study uses quantitative methods with associative techniques. The research subjects are food and beverage sub-sector companies listed on the IDX. The sampling technique was purposive sampling. The research sample amounted to 29 companies. The data obtained were analyzed by multiple linear regression analysis. The results showed that short-term debt and company age partially did not affect the company's profitability, while long-term debt and company size had a significant effect on company profitability. Short-term debt, long-term debt, company age, and company size simultaneously have a significant effect on company profitability.